Childhood and Child Labour in the British Industrial Revolution. - Humphries, J (Cambridge University Press, 2010)
This is an account of working-class childhood during the British industrial revolution. Using more than 600 autobiographies written by working men of the eighteenth and nineteenth centuries the author illuminates working-class childhood in contexts untouched by conventional sources and facilitates estimates of age at starting work, social mobility, the extent of apprenticeship and the duration of schooling. The classic era of industrialisation, 1790–1850, apparently saw an upsurge in child labour. While the memoirs implicate mechanisation and the division of labour in this increase, they also show that fatherlessness and large subsets, common in these turbulent, high-mortality and high-fertility times, often cast children as partners and supports for mothers struggling to hold families together. The book offers unprecedented insights into child labour, family life, careers and schooling. Its images of suffering, stoicism and occasional childish pleasures put the humanity back into economic history and the trauma back into the industrial revolution.